2019
DOI: 10.1136/bmjpo-2018-000398
|View full text |Cite
|
Sign up to set email alerts
|

What do families want to improve in the management of paediatric febrile neutropenia during anti-cancer treatment? Report of a patient/public involvement group

Abstract: BackgroundThis study reports how parents and young people who had an experience offebrile neutropenia (FN) improved the design of a trial to inform the management of this condition. Five parents, a young person who had completed treatment and three clinician-researchers contributed.MethodsThe group was formed after an invitation on social media and met via video conference. Many participants were from an existing childhood-cancer parent-involvement group. The initial questions asked during discussion were abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 16 publications
(23 reference statements)
0
35
0
Order By: Relevance
“…Various pathways for reduced-intensity treatment of children with low-risk FN have been explored, ranging from entirely homebased management to early discharge after a period of in-hospital observation with either oral or intravenous antibiotics [4,46]. While these options have been shown to be safe in randomised trials, studies using more stringent risk assessment demonstrate lower rates of treatment failure [4].…”
Section: Discussionmentioning
confidence: 99%
“…Various pathways for reduced-intensity treatment of children with low-risk FN have been explored, ranging from entirely homebased management to early discharge after a period of in-hospital observation with either oral or intravenous antibiotics [4,46]. While these options have been shown to be safe in randomised trials, studies using more stringent risk assessment demonstrate lower rates of treatment failure [4].…”
Section: Discussionmentioning
confidence: 99%
“…When deciding the optimal management strategy in paediatric practice, in addition to medical outcomes and cost implications, it is important to incorporate family/parental preferences. A survey of parental views showed that >75% of parents preferred at least some of the treatment to be hospital based,16 with focus group studies confirming a general preference for admissions to be as short as possible without compromising safety 17 18. Our strategy acknowledges this preference as all patients stay in hospital for at least 48 hours.…”
Section: Discussionmentioning
confidence: 87%
“…Parents report 30% was fine, some even as much as 50%. For them, the 50% chance of not having to come back was far more important 1. The reverse may be true when it comes to medication safety; we will accept that a drug may cause an adverse reaction in 1%–2% and describe it as safe; ‘normal’ people may read safe as ‘doesn’t cause harm’.…”
Section: Words Mattermentioning
confidence: 99%